Medical geo analysis of epidemical curve for emerged Corona epidemic and the suggested strategies to limit its spread - Hanan Subhi Addallah Obaid; Amal Saleh Abood Alkabi; Ibrahim Taha Alajloni ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
This study aimed at a geopolitical analysis of the epidemiological curve of the emerging Corona pandemic, propose strategies to limit its spread worldwide, track its traceable paths, and indicate the most important factors affecting its occurrence and spread.    Corona Disease is an acute respiratory syndrome caused by various types of viruses such as: Corona 229E virus, OC43 Corona virus, SARS virus 2003, Corona virus NL63 2004, HKU1 virus 2005, Corona virus that called Middle East Respiratory Syndrome (MERS) in 2012, and new corona virus nCoV-19.This virus was discovered for the first time in the sixties, it is one of the common diseases between humans and animals. Some of its types are transmitted from certain treasured animals, such as birds and some types of mammals, as it is transmitted between humans from the infected person to the healthy person.         The disease first appeared in the Chinese city of Wuhan in late December 2002. It was believed that the virus had initially transmitted from animals to humans and soon exceeded geographical boundaries to spread in almost all countries of the world.  The epidemiological importance of the disease is evident by its rapid spread and its ability to develop new strains that are not treatable, and the risk of complications resulting from both leads to a high death rate among those with it if they are not treated on time, especially the elderly and those with chronic diseases, and these are the most groups vulnerable to the risk of disease due to weakened immunity.    Cold, humid climatic conditions help increase the activity of viruses that cause disease. Congested environments create opportunities for transmission between people. Transfer and travel is one of the most important means of spreading infection from one place to another.Regarding the epidemiological situation of the Covid 19 pandemic compared to SARS and Middle East respiratory syndrome, it is spreading very quickly. While the outbreak of Middle East respiratory syndrome took about two and a half years to infect 1000 people, and SARS took about four months, the new Corona virus reached this number within 48 days only. However, current data indicate that this disease is less deadly than the previous two diseases, even though the current disease outbreak has led to the death of large numbers of people worldwide. One of the results of the study is to suggest strategies to limit the spread.